Differences Exudates After Irrigation With Measured Pressure on Diabetic Ulcers - Noor, Mohammad Arifin; Suyanto, Suyanto (Universitas Muhammadiyah Semarang, 2019)
Diabetic ulcer is a further complication of the presence of diabetic ulcers that are not handled properly. Gangren ulcers are very difficult to cure. One of them is the characteristic of gangrene wounds that have a hollow (hard) that is very difficult to do cleansing. In addition, the types of bacteria that are in gangrene are anaerobic bacteria that are difficult to treat with antibiotics. The number of bacteria will also be proportional to the number of production of pus. One of the most possible actions is to irrigate the wound tunnel so that the wound is clean and anaerobic bacteria are reduced. The modern wound irrigation device, which is one of the developments of existing irrigation devices, is expected to be able to reach gangrenous wound tunnels with a modified form of output. This study aimed to determine the effect of modification of the output of the modern wound irrigation device (MWID) on the number of bacteria in diabetic gangrenous ulcer sufferers. The method used in this study was quasi-experimental without a control group. The intervention group was given wound irrigation using a modified MWID tool. The instrument was used to determine exudate production using the observation sheet Leg Ulcer Measurement Tool (LUMT). The results of the analysis by the Mc Nemar test showed that p value 0.67 (p value> 0.05) means that there is no difference in the amount of exudate production with modification of the MWID output. Further research is needed regarding the effect of irrigation angle on the number of bacteria in diabetic ulcers.